Diabetes-associated autoantibodies among young diabetes mellitus patients in Malaysia - Mahayidin, Hasni; Zakariah, Siti Zulaikha; Ishah, Noor Ashidah; Wee, Xu Ann; Mohamed Nor, Nurhanani; Arip, Masita (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Diabetes-associated autoantibodies (DAA) is the hallmark of T1DM and LADA which are frequently tested in young diabetes patients. It was noted that up to 10-15% of patients with initial diagnosis of T2DM also exhibit DAA. Regardless of the classification, the presence of DAA suggests an underlying islet autoimmunity which lead to progressive pancreatic β-cell failure. There is limited data reported on DAA in young diabetes patients in Malaysia. This study aims to determine the frequency of DAA positivity and its association with demographic and clinical characteristics among this cohort. Methods: A retrospective study using secondary data obtained from Allergy and Immunology Research Centre, Institute for Medical Research, Malaysia. This study included 194 diabetes patients who were diagnosed before the age of 40 years old and tested for GADA, ICA, IA2A and IAA. Results: From 194 patients, 91 (46.9%) were positive for least one of the following DAA: ICA (79, 40.7%), GADA (61, 31.4%), IA2A (37, 19.1%) and IAA (9, 4.6%). Multiple positivity was higher (73.6%) compared to single positivity. Highest combination of double positivity was ICA+GADA (54, 59.3%) and triple positivity was ICA+GADA+IA2A (25, 27.5%). Simultaneous positivity of four autoantibodies was seen in only one (1.1%) patient. ICA, GADA and IA2A were associated with age group and ethnicity (all p < 0.001). Only IA2A was associated with gender (p = 0.012). Conclusions: GADA, ICA ad IA2A are more significant in young Malaysian diabetes patients. IAA has a very low frequency in this studied population.